Hubungan antara Efikasi Diri dengan Tingkat Kecemasan Perawat dalam Menghadapi Pandemi Covid-19 - Wedri, Ni Made; Sasmayaswari, GAA Divasya; Rasdini, IGA Ari (Jurnal Kesehatan, 2022)
Nurses are one of the health workers who have a role as the front liner in handling Covid-19. Currently, Covid-19 is a disease with a high risk of transmission for nurses who are in a state of exhaustion, psychological problems, and extraordinary stress so that their anxiety level in dealing with the Covid-19 pandemic increases. Self-efficacy can help nurses provide health services in situations like this. The purpose of this research was to determine the relationship between self-efficacy and the level of anxiety of nurses in facing the Covid-19 pandemic at BRSUD Tabanan. The research design used correlational analytics with the cross-sectional approach. The sample in this study amounted to 79 people using the purposive sampling technique. Self-efficacy was measured using the GSES questionnaire and anxiety levels were measured using the HARS questionnaire. The results showed that 92.4% of the respondents were female, between the ages of 26-35 years as many as 41.8%. The mean score of respondents' self-efficacy shows that the category of self-efficacy is very high. The average score of the respondents' anxiety level shows low anxiety. The results of the Pearson product-moment correlation test resulted in a value of r=-0.962 (p-value=0.000). This study concludes that there is a negative, strong, significant relationship between self-efficacy and anxiety levels. It is expected that nurses will always maintain and maintain self-efficacy